Improving Civics Activities and Learning Outcomes by Applying the Numbered Heads Together (NHT) Learning Model - Nita Suriyani Etta (Pinisi Journal of Education and Management, 2022)
Numbered Head Together is a cooperative learning model that uses numbers placed above the head with the aim of making it easier for teachers to explore student activities in finding, processing, and reporting information from various sources which is finally presented in front of the class. The purpose of this study is to describe the application of the Numbered Heads Together learning model so that it can improve activities and learning outcomes of Civics Class XII MIPA 2 SMA Negeri Terpadu Madani Palu in the odd semester of the 2021/2022 academic year. This research is a classroom action research. The research subjects are students of class XII MIPA 2 SMA Negeri Model Terpadu Madani Palu totaling 18 people consisting of 7 boys and 11 girls. Or equivalent to 50% of the number of students in the class. While the research procedure consists of 4 stages, namely: planning, implementation, observation, and reflection. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and data verification/conclusion. The results showed that the application of the Numbered Heads Together model could increase the activities and learning outcomes of Civics Class XII MIPA 2 SMA Negeri Terpadu Madani Palu in the odd semester of the 2021/2022 academic year.